The Problem of Anaemia in Patients with Colorectal Cancer. (12th February 2014) - Khanbhai, M.; Shah, M.; Cantanhede, G.; Ilyas, S.; Richards, T.
Abstract : Background . Surgical patients are often anaemic preoperatively subsequently requiring blood transfusion. The aim of this study was to assess the problem of anaemia and transfusion rates in patients undergoing surgery for colorectal cancer. Methods . Haemoglobin levels and transfusion requirements were assessed retrospectively in 199 sequential patients operated on for colorectal cancer. This was followed by prospective analysis of 147 patients to correlate preoperative anaemia, stage of bowel cancer, and operation performed with rates of blood transfusion and length of hospital stay. Results . Preoperatively 44% patients were anaemic retrospectively and 60% prospectively. Anaemia increased the risk of transfusion in both studies (69% anaemic versus 31% nonanaemic, P = 0.002 in retrospective series, and 83.7% versus 16.3%, P < 0.0001 in prospective series). Anaemia was proportionally higher in patients with Dukes B (65.2%) and Dukes C (66.6%) than in patients with Dukes A (28.5%). Length of stay was prolonged in transfused patients excluding those requiring major blood transfusion (median 13 versus 7 days, P < 0.0001 ). Transfusion was also associated with higher mortality (P = 0.05 ). Conclusion . Anaemia is common in patients with colorectal cancer. Anaemic patients were at high risk of receiving blood transfusion, which in turn increased length of stay and mortality.